1985
DOI: 10.1136/ard.44.9.603
|View full text |Cite
|
Sign up to set email alerts
|

Decreased nailfold capillary density in Raynaud's phenomenon: a reflection of immunologically mediated local and systemic vascular disease?

Abstract: SUMMARY Nailfold capillary patterns were studied in 107 patients with Raynaud's phenomenon (RP), including patients with (n=39) and without (n=68) connective tissue disease (CTD). Capillary density was decreased in patients with sclerodactyly, digital ulcers, tuft resorption, and telangiectasia, compared with patients without these symptoms. In addition, an inverse relationship was found between the severity of RP at first presentation (as graded by photoelectric plethysmography during cooling) and the capilla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0
4

Year Published

1986
1986
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 20 publications
2
12
0
4
Order By: Relevance
“…Pattern and frequency of widefield nail fold capillary changes in patients with PSS were similar to those described previously [1,2,4,7,9,11], Two of these studies could not demonstrate a relationship between capil lary changes and organ involvement [11,12]. Lovy et al [11] reported a correlation be tween extreme capillary loss and mean dura tion of the disease, but without a significant correlation between the presence or the severity of capillary enlargement and the ex tent of organ involvement in 42 patients [12].…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Pattern and frequency of widefield nail fold capillary changes in patients with PSS were similar to those described previously [1,2,4,7,9,11], Two of these studies could not demonstrate a relationship between capil lary changes and organ involvement [11,12]. Lovy et al [11] reported a correlation be tween extreme capillary loss and mean dura tion of the disease, but without a significant correlation between the presence or the severity of capillary enlargement and the ex tent of organ involvement in 42 patients [12].…”
Section: Discussionsupporting
confidence: 67%
“…In contrast, 3 other former studies disclosed a correlation between capillary en largement or loss and organ involvement and appearance of ANA. In the opinion of these authors, these nailfold capillary changes mirror a systemic vascular disease [5,12,13]. In our patients, we found a high correla tion between capillary enlargement or loss and visceral involvement or immunological findings.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Apesar de diversos estudos relatarem associação da dilatação capilar ou desvascularização na CPU com lesões em órgãos internos (5,(8)(9)(10)(11)(12)(13)(14)(15)(16) , outros falharam em reproduzir esses achados (4,17,18,22) . A ampla variabilidade nos resultados devese possivelmente a diferenças amostrais e a diferentes métodos de aferição de alterações clínicas e da CPU.…”
Section: Discussionunclassified
“…Diversos estudos tentaram associar a presença ou severidade de alterações capilaroscópicas com lesões em órgãos-alvo na ES, obtendo resultados variáveis (4,5,(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) . Nenhum desses estudos tentou associar os achados capilaroscópicos com alterações na tomografia computadorizada de alta resolução (TCAR) pulmonar, que é um método muito mais sensível e precoce do que a radiografia de tórax para a detecção de doença intersticial pulmonar (19) .…”
Section: Introductionunclassified